From the Decision Conciliation to the Dispute Resolution Board: Notes in relation to the Dispute Resolution Board as a New Method of Conflict Resolution for a Formalized Work Contract Under the scope of the New Public Procurement Law - Hurtado Falvy, Juan Manuel (2015)
The new Public Procurement Law introduces the Dispute Boards as a new settlement ofdisputes and contestations during the contractual execution of the work phase. The present article works, in the first place, the framework of public procurement and the controversies that are originated in the matter. Then, it will expose the development of the Dispute Boards in other countried and their characteristics. Finally, it concludes identifying the type of Dispute Boards that is being adopted in Peruvian law, showing his vantages and disadvantages.